Digital marketing communication of Somethinc brand on instagram @somethincofficial - Cindy Novita Chandra; Daniel Susilo; Teguh Dwi Putranto (Faculty of Communications Science, Dr. Soetomo University, 2023)
The advent of the digital era has spurred numerous companies to employ marketing communications strategies. Such endeavours serve as a means to influence and remind consumers about the array of products or services they offer. A particularly prominent approach for companies entails utilising digital marketing communications. In this context, the focus extends beyond mere product promotion; instead, it centres on disseminating valuable, pertinent, and consistent content to captivate and retain consumers. For this study, Instagram has been selected as the platform of interest due to its prevalence as a content distribution channel. The primary objective of this research is to explore the practices of digital marketing communications employed by the Something brand through its Instagram presence. To this end, the Krippendorff content analysis method has been applied to discern the nature of posts related to digital marketing communications on the official Instagram account @somethincofficial. The analysis was conducted on posts from 1 August 2022 to 31 October 2022. The study's findings reveal that Somethinc's digital marketing communication practices on Instagram predominantly revolve around informative and reminding advertising. These strategies are pivotal in engaging the audience and reinforcing brand awareness on the platform.